A COMPETENCIES POSSESSED BY OFFICE TECHNOLOGY AND MANAGEMENT LECTURERS IN POLYTECHNICS IN ANAMBRA AND ENUGU STATES (NAU Journal of Technology and Vocational Education, 2024)
This study sought to assess the tele-communication and media competenciespossessed by OTM lecturers in tertiary institutions in Anambra and Enugu states. Thestudy adopted a descriptive survey design. Two research questions guided the study whiletwo hypotheses were tested at 0.05 level of significance. The population consisting of 38OTM lecturers was studied. A validated questionnaire with reliability coefficients of 0.71and 0.84 was used for data collection. The arithmetic mean and standard deviation wereused to analyze the data in respect of the research questions while ANOVA was used totest the hypotheses. It was found that respondents possessed both tele-communication andmedia competencies at a low extent. The researchers' conclude that the respondents canhardly produce graduates with tele-communication and media competencies. It isrecommended, among others, that management of Polytechnics should provide adequatetechnological resources, technical and administrative support to encourage OTMlecturers to successfully use ICT in classrooms.
Keywords: Assessment, tele-communication competencies, media competencies, OTM, tertiary institutions